Chang'an 26 BCE : An Augustan Age in China - Loewe, Michael; Vankeerberghen, Griet, 1964-; Nylan, Michael (Book collections on Project MUSE., 2015)
"The northern Chinese city of Chang'an, located near today's Xi'an, was the capital of multiple dynasties. At its zenith during the Western Han dynasty, before an interregnum period divided the dynasty into the Western/Former Han (202 BCE-9 CE) and Eastern/Later Han (25-220 CE), Chang'an was nearly three times the size of Rome and nearly four times larger than Alexandria. Although thousands of studies document imperial Rome's glory, no book-length work in a Western language is devoted to Chang'an, even though the two cities had comparable numbers of capital residents and imperial subjects and comparably vast territories. Chang'an 26 BCE addresses this deficiency, using the reign period of Emperor Chengdi (r. 33-7 BCE) and the year in which the Imperial Library Project began (26 BCE) as a focal point. Such a volume is possible now through correlation of archaeological and literary records relating to several decades in the capital region, when the Western Han capital flourished brilliantly before it was partially razed in 23 CE. This first in-depth survey by some of the world's best scholars, Chinese and Western, builds a case for the need to revise historical assumptions about the two Han dynasties"--Provided by publisher.